2013
DOI: 10.1136/vr.100833
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii viability and efficacy in horses with antimicrobial‐induced diarrhoea

Abstract: Saccharomyces boulardii has been successfully used in the prevention and treatment of antimicrobial-associated diarrhoea in humans. We hypothesised that a viable, dried lyophilised preparation of S boulardii would survive in the gastrointestinal tract of horses with antimicrobial-associated enterocolitis, and significantly decrease the duration of diarrhoea. Twenty-one horses, over one year of age, with antimicrobial-associated diarrhoea of up to 72 hours duration, were consecutively randomised in a controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
0
34
0
2
Order By: Relevance
“…The effect of probiotics in horses with enteric disease might differ from the effect in healthy horses, but no adverse clinical effects were reported in horses with gastrointestinal disease . Based on the above data, most authors consider probiotics, particularly S. boulardii, safe for use in healthy and diseased adult horses …”
Section: Safety Of Probioticsmentioning
confidence: 99%
“…The effect of probiotics in horses with enteric disease might differ from the effect in healthy horses, but no adverse clinical effects were reported in horses with gastrointestinal disease . Based on the above data, most authors consider probiotics, particularly S. boulardii, safe for use in healthy and diseased adult horses …”
Section: Safety Of Probioticsmentioning
confidence: 99%
“…Probiotics have been shown to reduce the incidence of diarrhoea in foals [11,12], but other studies have found a higher incidence of diarrhoea requiring veterinary attention in neonatal foals [13,14]. Several studies were unable to show beneficial effects of probiotic administration in prevention or treatment of diarrhoea in adult horses [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics exert their beneficial effect through several pathways, including production of antimicrobial compounds targeting intestinal pathogens and their toxins, as well as general immune stimulation and colonization resistance 6. Few studies in horses have been performed to date to evaluate the efficacy of probiotics in prevention or treatment of enteric disease 4, 7, 8. The 2 studies on probiotic use to prevent neonatal foal diarrhea failed to show a lack of significant effect of probiotic treatment 3, 9.…”
mentioning
confidence: 99%